Thermal decomposition of benzaldehyde diperoxide in isopropyl alcohol, effect of solvent polarity - Profeta, Mariela Inés (2015)
Fil: Profeta, Mariela Inés. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.